Roma in/of Romania: A Brief Overview - Chiriţoiu, Ana (Romano džaniben, 2025)
The introduction to the thematic issue provides a comprehensive overview of current knowledge about Romanian Roma, the largest Roma population in Europe. The author summarizes key themes in scholarly and popular literature by Romanian (Roma and non-Roma) authors, especially historical forms of oppression—centuries of enslavement, the Romani Holocaust, and the policies of the communist regime—and their long-term impacts on contemporary social exclusion. The text highlights the persistence of structural antigypsyism, manifested in housing, education, health, and employment, and situates it within the theoretical frameworks of critical Romani studies and the political economy of poverty. It also maps the phenomenon of Roma migration and transnational family networks after 1990, European states’ responses to Roma mobility, and the effects of the COVID-19 pandemic. A significant section is devoted to contemporary Romani artistic production, particularly theatre and literature, which challenge stereotypes and amplify the voices of Romani actors. The study thus weaves together historical, social, and cultural perspectives to offer both specialist and general audiences a multifaceted portrait of Romanian Roma.